Learning a Healthy Rhythm: An Intervention to Increase Children's Resources for Stress Management. (January 2023) - Haglund, Kristin; King, Amanda L.; Bekhet, Abir K.; Garnier-Villarreal, Mauricio; Olson, Karen; Atshan, Rasha; Ortiz, Angela; de los Santos, Johanna; Belknap, Ruth Ann
This article describes a pilot test of a community engaged, culturally relevant, arts-based intervention. The purpose was to increase children's personal protective buffering resources. Protective buffering resources help children cope with stressful stimuli, reduce activation of their systemic stress response, mitigate allostatic load, and promote optimal health. The "Learning a Healthy Rhythm" intervention included a stress management component and an ongoing Afro-Latino percussion program for 18 children ages 9–11. The stress management component included educational content about stress, self-assessment of stress symptoms, and stress management techniques. A mixed-method intervention evaluation design was used. Qualitative data, quantitative data, and biometrics including hair cortisol were collected. Six intervention parameters were evaluated: effectiveness, fidelity, feasibility, acceptability, necessity, and safety. Positive results were obtained for all parameters. Reduction in physiological and subjective measures of stress was evident. This stress management intervention was well-received and supported by participants.